2021
DOI: 10.1101/2021.01.11.426196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex phyllosphere microbiome aids in the establishment of the invasive macrophyteHydrilla verticillata(L.) under conditions of nitrogen scarcity

Abstract: Despite the low availability of nitrogen (N), the highly productive macrophyte Hydrilla verticillata (L.) is a successful invader of the littoral zones at lake Atitlán, Guatemala, with profound implications for lake ecology. To help answer the question of how Hydrilla, accompanied by the filamentous green alga Cladophora Kützing (Ulvophyceae), sustains fast growth under conditions of N scarcity, we studied the composition and potential biogeochemical function of the associated microbiomes. We combined results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…( 2021b , 2021 ) reported that the phyllosphere microbiome is involved in the transmission of antibiotic resistance genes in the urban green facade. Another report (Bárta et al ., 2021 ) suggests that the phyllosphere microbiome aids in the establishment of the invasive macrophyte Hydrilla verticillata L. under conditions of nitrogen scarcity. Increasing evidence shows that global change has pervasive impacts on plant health and ecosystem functioning, and harnessing the beneficial functions provided by the phyllosphere microbiome to enhance plant growth and fitness to face such impacts is considered a viable sustainable approach.…”
Section: Ecological Functions Of the Phyllosphere Microbiomementioning
confidence: 99%
“…( 2021b , 2021 ) reported that the phyllosphere microbiome is involved in the transmission of antibiotic resistance genes in the urban green facade. Another report (Bárta et al ., 2021 ) suggests that the phyllosphere microbiome aids in the establishment of the invasive macrophyte Hydrilla verticillata L. under conditions of nitrogen scarcity. Increasing evidence shows that global change has pervasive impacts on plant health and ecosystem functioning, and harnessing the beneficial functions provided by the phyllosphere microbiome to enhance plant growth and fitness to face such impacts is considered a viable sustainable approach.…”
Section: Ecological Functions Of the Phyllosphere Microbiomementioning
confidence: 99%
“…For instance, phyllosphere microorganisms involved in the transmission of ARGs in the urban green facade 135 and the reproduction of the invasive macrophyte Hydrilla verticillata L. under conditions of nitrogen scarcity. 136…”
Section: Ecological Functions Of Phyllospherementioning
confidence: 99%
“…On the other hand, some studies show negative impacts of phyllosphere microorganisms on the host. For instance, phyllosphere microorganisms involved in the transmission of ARGs in the urban green facade and the reproduction of the invasive macrophyte Hydrilla verticillata L. under conditions of nitrogen scarcity …”
Section: Ecological Functions Of Phyllosphere Microorganismsmentioning
confidence: 99%